Intramolecular electron transfer reactions in meso-(4-nitrophenyl)-substituted subporphyrins. Issue 7 (8th December 2015) - Copley, Graeme; Oh, Juwon; Yoshida, Kota; Shimizu, Daiki; Kim, Dongho; Osuka, Atsuhiro
Abstract : A2 B-type meso -(4-nitrophenyl)-substituted subporphyrins have been synthesized and shown to undergo very fast photoinduced intramolecular charge separation (CS) and charge recombination (CR) between the subporphyrin core and the meso -4-nitrophenyl group in CH2 Cl2 as probed by femtosecond time-resolved transient absorption spectroscopy. Abstract : A2 B-type meso -(4-nitrophenyl)-substituted subporphyrins have been synthesized and shown to undergo very fast photoinduced intramolecular charge separation (CS) and charge recombination (CR) between the subporphyrin core and the meso -4-nitrophenyl group in CH2 Cl2 as probed by femtosecond time-resolved transient absorption spectroscopy. Red-shifted emissions were detected from charge-separated states as a rare case for porphyrinoids.